Implications of the word "grieve" in the Koran applied study - Benchabane, Abdelghani (Journal of Human Sciences, 2021)
This study attempts to monitor the meanings of the word "Yahznoun" (They grieve) in the Holy Quran through the various structures and contexts in which it was presented.